Rainfall asymmetry in the southeast Indian Ocean between positive and negative IODs and its local impact. (16th December 2013) - Gao, Libao; Yu, Weidong; Li, Tim; Adi, T. R.; Budi, S.; Triyono,; Salvienty, M.
Abstract The analysis of Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI) satellite observations and European Centre for Medium‐Range Weather Forecasts (ECMWF) reanalysis data identify an asymmetric rainfall pattern in the southeast Indian Ocean (SEIO) between the positive and negative Indian Ocean Dipoles (IODs). During positive (negative) IODs, the precipitation anomaly is more confined to equatorial (off‐equatorial) regions, even though their associated sea surface temperature anomalies almost reside in the same region. It is argued that the rainfall pattern asymmetry is attributed to the effect of the rainfall mean state. While the negative rainfall anomalies associated with positive IODs are confined in the region of mean precipitation, the positive rainfall anomalies associated with negative IODs do not have such a constraint. The so‐induced asymmetric rainfall pattern exerts a great impact on the upper ocean salinity and bushfires over the western maritime continent.